2010
DOI: 10.1007/s00420-010-0523-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socioeconomic factors and human activities on children’s PM10 exposure in inner-city households in Korea

Abstract: We found that indoor PM(10) concentrations were affected by socioeconomic factors rather than human behavioral activities. In determining the environmental policy for indoor air quality, it is important to consider various socioeconomic factors of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
1
16
2
6
Order By: Relevance
“…These trends were found in asthma and allergic rhinitis, but they were not significant. People in underprivileged groups are frequently exposed to indoor pollutants and may have high risks of asthma and allergic diseases [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…These trends were found in asthma and allergic rhinitis, but they were not significant. People in underprivileged groups are frequently exposed to indoor pollutants and may have high risks of asthma and allergic diseases [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, the mean PM 4 concentrations in smoker households amounted in winter and summer, for instance, to 109 µg/m³ and 59 µg/m³ respectively, and in non smoker households they amounted during the two seasons only to 28 µg/m³ (Fromme et al, 2005). Other important influencing factors for the indoor air contents are the season, the outdoor air, the ventilation behaviour, the age and the location of the buildings and indoor activities such as cooking, the use of ovens and the burning of incense sticks (Mönkkönen et al, 2005;Martuzevicius et al, 2008;Santen et al, 2009;Rodes et al, 2010;Héroux et al, 2010;Byun et al, 2010;Raaschou-Nielsen et al, 2011).…”
Section: Particles In Residencesmentioning
confidence: 99%
“…Besides, it should be noticed that the exposure to air pollutants is not equal for all population subgroups even in the same region. A large number of studies have revealed the associations between socio-economic status (SES) factors (e.g., household income and employment status) and personal exposure or the concentrations in micro-environments [13,14]. Hence, the influence of SES variables should be taken into account when estimating the exposure to both pollutants.…”
Section: Introductionmentioning
confidence: 99%